Increasing the strength of grey cast iron by introducing of dispersed additives into the melt - F. I. Rudnitsky; S. A. Kulikov; V. A. Shumigai (Литьë и металлургия)
The basic mechanisms of increasing the strength of alloys, including methods through the introduction of the melt coherent and incoherent crystallizing structural components of the alloy dispersed particles were considered. New data on the influence of ultrafine particles obtained from grinding wastes of tool steels (metal abrasive slime) and proposed as modifying additives on the structure and strength properties of gray cast iron are presented. The prevailing influence of metal component of metal-abrasive sludge on the properties of cast iron is revealed. The optimum amount of additives-modifiers were defined. The increase in the strength of cast iron mid 20 as a result of modification is equal up to 20%